2023
DOI: 10.1038/s41467-022-35204-6
|View full text |Cite
|
Sign up to set email alerts
|

Salp blooms drive strong increases in passive carbon export in the Southern Ocean

Abstract: The Southern Ocean contributes substantially to the global biological carbon pump (BCP). Salps in the Southern Ocean, in particular Salpa thompsoni, are important grazers that produce large, fast-sinking fecal pellets. Here, we quantify the salp bloom impacts on microbial dynamics and the BCP, by contrasting locations differing in salp bloom presence/absence. Salp blooms coincide with phytoplankton dominated by diatoms or prymnesiophytes, depending on water mass characteristics. Their grazing is comparable to … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
19
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 29 publications
(22 citation statements)
references
References 97 publications
2
19
0
Order By: Relevance
“…Our results also align with a recent study from the Sargasso Sea showing that zooplankton size did not correlate with export flux (Perhirin et al, 2024). That study also showed that opacity was an important zooplankton trait that correlated strongly with export flux, and although we could not quantify opacity from our dataset, several of our highest export efficiency locations (from the SalpPOOP cruise, Décima et al, 2023) were measured within a bloom of highly transparent pelagic tunicates. We further note that our sinking particle measurements do not include the potential impact of zooplankton carcasses, which can be substantial in some regions (Frangoulis et al, 2011;Halfter et al, 2022;Smith et al, 2014) and would covary with abundance of large taxa.…”
Section: Discussionsupporting
confidence: 91%
“…Our results also align with a recent study from the Sargasso Sea showing that zooplankton size did not correlate with export flux (Perhirin et al, 2024). That study also showed that opacity was an important zooplankton trait that correlated strongly with export flux, and although we could not quantify opacity from our dataset, several of our highest export efficiency locations (from the SalpPOOP cruise, Décima et al, 2023) were measured within a bloom of highly transparent pelagic tunicates. We further note that our sinking particle measurements do not include the potential impact of zooplankton carcasses, which can be substantial in some regions (Frangoulis et al, 2011;Halfter et al, 2022;Smith et al, 2014) and would covary with abundance of large taxa.…”
Section: Discussionsupporting
confidence: 91%
“…Unknown particles matching this description were also described by both Madin and Purcell (1992) and Ahmad-Ishak et al (personal communication) and can be seen in the SEM images taken by Caron et al (1989) although they were not discussed. Due to their size and generally spherical shape, we assume that the majority of these particles were nanophytoplankton such as prasinophytes, prymnesiophytes, or pelagophytes for which characteristic features such as flagella had been digested or broken off as these groups had a high abundance and contribution to phytoplankton community biomass (Décima et al 2023). It is, however, likely that this morphological categorization includes particles of various origins.…”
Section: Discussionmentioning
confidence: 99%
“…Samples were collected over Aotearoa New Zealand’s Chatham Rise during October 21 - November 21 2018 as part of the Salp Particle Export and Ocean Production (SalpPOOP) study, which was designed to investigate how salps affect the ecology and biogeochemistry of the region (Décima et al 2023). The Chatham Rise is notable because it sits within the Subtropical Front of the southwest Pacific, which defines the boundary between warm, salty and low-nitrate subtropical waters and cold, fresh, nitrate-rich, and iron-poor subantarctic waters (Zentara and Kamykowski 1981; Heath 1985; Sokolov & Rintoul 2009;).…”
Section: Methodsmentioning
confidence: 99%
“…"Jelly-falls", defined as the sinking of gelatinous zooplankton carcasses in the water column following a swarming event, can result in the export of huge amounts of organic matter to the seafloor (Lebrato et al, 2012(Lebrato et al, , 2019Luo et al, 2020;Sweetman et al, 2014;Sweetman & Chapman, 2015). In particular, recent studies suggest that FFGM may play a central role in deep ocean carbon fluxes (Clerc, Bopp, Benedetti, et al, 2023;Décima et al, 2023;Henschke et al, 2016;Luo et al, 2022;Steinberg et al, 2023). Their role in the carbon cycle in a changing climate remains unknown.…”
Section: Introductionmentioning
confidence: 99%